The Development of an Innovative Learning Method with Augmented Reality Applications on Smartphone - Chaleoykitti, Saisamorn; Chiewsothorn, Sarintorn; Nuyleis, Yada (Nursing Research and Innovation Journal, 2019)
This article aimed to present the development of an innovative learning method with Augmented Reality (AR) applications on Smartphone to transfer knowledge for students in the Mental Health and Psychiatric Nursing course, Bachelor of Nursing Science Program, the Royal Thai Army Nursing College. This innovative virtual learning media that students learn through the application on the smartphone is in the early stage of development. Some topics were completed including therapeutic relationship, substance use problem and treatment, and emergency psychiatry nursing care. From this work, it is found that this teaching-learning method is useful for the generation Z nursing students. The authors deliver the virtual media instructional process using smartphone and the process of using for readers to study and apply it as appropriate. Keywords: Innovative virtual teaching, Augmented reality, Application, Smartphone, Psychiatric nursing